1970
DOI: 10.1128/jvi.6.4.400-405.1970
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Replication Complex of Bacteriophage P22

Abstract: A replication complex for the vegetative synthesis of the deoxyribonucleic acid (DNA) of the temperate phage P22 previously has been described. This complex is an association of parental phage DNA, most of the newly synthesized phage DNA made during pulses with 3H-thymidine, and other cell constituents, and has a sedimentation rate in neutral sucrose gradients of at least 1,000S. The complex is one of the intermediates, intermediate I, in the synthesis and maturation of phage P22 DNA after infection or inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1971
1971
1978
1978

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…A third hypothesis involves the P22 replication complex, or intermediate I (1,8). This replication complex is a rapidly sedimenting association of parental phage DNA, newly synthesized phage DNA, and various cellular constituents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third hypothesis involves the P22 replication complex, or intermediate I (1,8). This replication complex is a rapidly sedimenting association of parental phage DNA, newly synthesized phage DNA, and various cellular constituents.…”
Section: Discussionmentioning
confidence: 99%
“…The replication complex, also known as intermediate I, is a rapidly sedimenting association of phage DNA and various cellular constituents (1). All phage DNA synthesis takes place in intermediate I. Ts25.1 is a mutation which prevents the association of parental phage DNA with intermediate I at restrictive temperatures (8). Ts25.1 mutants carry out no known phage functions other than adsorption and injection (Hoffman and Levine, iuniplublished data).…”
Section: Methodsmentioning
confidence: 99%
“…It should be possible to separate the early activities required for viable phage production from those that occur late in I Present addres: Virology Section, The Weizmann Institute of Science, Rehovot, Israel. infection (assembly). Temperature-sensitive mutants for gene 16 have been found and are described in this paper. P22 16-ts phages conform to the expected phenotype for mutant phage containing thermolabile P16 in the virion.…”
mentioning
confidence: 92%
“…We have characterized a mutant of P22 carrying a temperature-sensitive allele of gene 16. This mutant has previously been referred to as P2225-ts (Levine et al, 1970(Levine et al, , 1972 and P22 X-ts Soska, 1970, 1973). P22 16-ts behaves as an early mutant at the nonpermissive temperature.…”
mentioning
confidence: 99%
“…This complex, intermediate I, is an association of parental phage DNA, newly synthesized phage DNA, and other cell constituents. In a previous paper we have shown that, upon superinfection of P22 lysogens with the homoimmune phage, the input phage DNA does not associate with intermediate I (9). That this inhibition is due to the action of repressor was shown by good association of the superinfecting DNA with the complex after induction with ultraviolet light.…”
mentioning
confidence: 94%